MORPHOLOGICAL CHANGES IN DENTAL PULP WITH DIFFERENT DEPTHS OF TOOTH PREPARATION - Asrar Ahmed; Muhammad Sharjeel Ilyas; Sana Chaudhry et al. (Journal of University Medical & Dental College, 2017)
Abstract Objective: This study has been planned to know that under standardized tooth preparation procedure what immediate morphological changes are observed in a different clinical setting, which could be the cause of pulp necrosis later on. Materials and Methods: 140 intact premolars were used as a subject and were equally divided in four groups (One control and three experimental groups). In each experimental group different depth of tooth preparation procedure was done along with copious irrigation of water and new dental bur for each subject. The teeth were extracted after the procedure and were fixed in 10% formalin solution. Teeth specimens were processed in laboratory and slides were observed under the light microscope. Results: In terms of acute inflammatory infiltrate and necrosis 100 % success was observed as none of the study groups revealed this abnormality however other morphological changes including, vacuolated odontoblastic layer with disrupted nuclei, and vasodilatation were observed in all study groups. Chi Square test was applied as inferential statistics. Conclusion: Morphological changes do occur in all experimental groups. These changes become more severe and aggressive as the depth of tooth preparation is increased.